2006
DOI: 10.4102/ojvr.v73i2.162
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of natural ovine malignant theileriosis with a chloroform extract of the plant <i>Peganum harmala</i> : research communication

Abstract: One hundred sheep naturally infected with Theileria lestoquardi were treated with a chloroform extract of the plant Peganum harmala. The treatment was continued for 5 days, the dose of extract being 5 mg/kg per day. Sixty-five of the sheep responded to treatment and recovered but 35 did not and died. The cure rate was 65 %.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 3 publications
0
6
1
Order By: Relevance
“…In this study 100 % of the sheep recovered after treatment but in another experiment reported by Mirzaiedehaghi (2006), the recovery rate was 65 %. The reasons for this apparent discrepancy in the success rate of the treatment, could be the different environmental conditions, and the small numbers of sheep we used.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…In this study 100 % of the sheep recovered after treatment but in another experiment reported by Mirzaiedehaghi (2006), the recovery rate was 65 %. The reasons for this apparent discrepancy in the success rate of the treatment, could be the different environmental conditions, and the small numbers of sheep we used.…”
Section: Discussioncontrasting
confidence: 50%
“…Three days after a febrile reaction had developed and the detection of schizonts in the prescapular lymph node smears, treatment of the lambs in Group A with the alkaloids of P. harmala was commenced intramuscularly at a dose of 5 mg of the dried material in 0.1 ml normal saline/kg body mass (Mirzaiedehaghi, 2006) once daily for 7 days. The lambs in Group B were untreated and served as controls.…”
Section: Methodsmentioning
confidence: 99%
“…The recovery rate of cattle from theileriosis was 78%, but in our previous study on natural malignant theileriosis in sheep, it was 65% (Mirzaiedehaghi, 2006). The reason for this discrepancy in the success rate of these 2 studies could be attributed to the different extracts of P. harmala.…”
Section: Discussionmentioning
confidence: 80%
“…Treatment with the extract containing the alkaloids of P. harmala was performed intramuscularly at a dose of 5 mg/kg body weight once daily for 5 days (Mirzaiedehaghi, 2006). All cattle with rectal tempera-268 Korean J. Parasitol.…”
Section: Methodsmentioning
confidence: 99%
“…Other investigators have shown that trivalent antimonial compounds were highly toxic to different Leishmania species in the promastigote form at concentrations ranging from 1.58 to 35.00 μg of Sb (III)/mL (20)(21)(22). Several studies have shown that different protozoan infections have been susceptible to P. harmala extract in varying degrees (23,24). The our results showed that there was no significant difference between plants extract and Glucantime (P>0.05) in MTT and IC50 test also NO production.…”
Section: Discussionmentioning
confidence: 99%